THE PLACE OF DANCE IN THE PRESIDENT'S FIVE KEY INITIATIVES (British Journal of Global Ecology and Sustainable Development, 2024)
This article contains a philosophical analysis of the essence , practical significance of guarantees of equal rights and opportunities for women and men in the new constitution of the Republic of Uzbekistan. The priorities of the fair policy on the glorification of human dignity in our country have been studied.